(untitled) (PANGEEA, 2025)
“Groves” villages in Apuseni - structure and toponymy. The high-altitude villages of Apuseni Mountains, the house are grouped in “groves”, inhabited by the same family. The name of this villages is given by the surname of their form. Such situations are common in the Apuseni Mountains and shows the structure and evolution of the population of these villages.